Pengaruh Penambahan SWD Aplikasi Modifikasi Kontraplanar pada Intervensi Ultrasound dan Traksi Osilasi Shoulder terhadap Peningkatan Jumlah Range Of Motion (Rom) Shoulder Bidang Frontal dan Bidang Transversal Penderita Frozen Shoulder - Ade Irma N; Rida Yulianda (Pena Medika Jurnal Kesehatan, 2010)
Background : This study aims to determine the effect of adding modifications kontraplanar SWD applications, combined with a provision of ultrasound and traction oscillations shoulder toward Increasing Number of Range of motion (ROM), shoulder frontal plane and transverse On Frozen Shoulder Patients.Methode : The sample taken is the installation of physiotherapy patients Hospital physiotherapy Mintohardjo Navy Hospital, Jakarta totaling 14 people who are selected based on purposive sampling techniques were then divided into two intervention groups using the assessment tables are available. This was a kind of quasi-experimental research to determine effect of an intervention undertaken to research object. This research ststistik analysis used t-test to determine the effect of therapy related to the research sample at the same treatment group, and independent t-test as a test to compare differences between control and treatment groups.Result : Based on the results of independent t-test showed that there was no significant difference in effect between the intervention and traction oscillations Ultrasound Ultrasound and shoulder with shoulder with the addition of traction oscillations SWD kontraplanar modification application on Frozen Shoulder condition with P = 0.070 for the frontal plane and P = 0.185 for field trasnversal (P> 0.05). The intervention ultrasound and traction oscillations shoulder or shoulder ultrasound and traction oscillations with the addition of the modification application kontraplanar SWD had shown to increase due to frozen shoulder ROM, which can be used as an effective intervention selected that can be applied and developed in frozen shoulder condition. Keywords: frozen shoulder, traction oscillations, ultrasound, application kontraplanar SWD, ROM.